1987
DOI: 10.1016/0014-5793(87)80752-4
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of calcium binding to fura‐2 and indo‐1

Abstract: The kinetics of Ca2+ dissociation from fura-and indo-l were measured using a stopped-flow spectrofluorimeter. The dissociation rate constants were 84 s-t and 130 s-t, respectively, in 0.1 M KC1 at 20°C. The rate constants were insensitive to pH over the range 7.0 to 8.0. The second order association rate constants were estimated indirectly to be in the region of 5 x lo8 M-'.s-' and thus approach the diffusion-controlled limit. The results demonstrate that these new generation indicators are well-suited to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 11 publications
10
69
0
1
Order By: Relevance
“…To our knowledge, A major finding of our study is that the decay of the fluorescence transients continues throughout diastole and that a variety of pharmacologic and physiologic maneuvers that alter contractile force produces parallel changes in -1) is at least an order of magnitude faster than the decay of the fluorescence transients we observe (24).…”
Section: Discussionmentioning
confidence: 82%
“…To our knowledge, A major finding of our study is that the decay of the fluorescence transients continues throughout diastole and that a variety of pharmacologic and physiologic maneuvers that alter contractile force produces parallel changes in -1) is at least an order of magnitude faster than the decay of the fluorescence transients we observe (24).…”
Section: Discussionmentioning
confidence: 82%
“…7G,H ). Because of the rapid association kinetics of Ca 2ϩ binding to indo-1 (k on ϭ 5 ϫ 10 8 M/sec; Jackson et al, 1987), it is unlikely that the slow rise in the reported [Ca 2ϩ ] i is attributable to the inability of the Ca 2ϩ indicator dye to follow the rise in bulk [Ca 2ϩ ] i . Moreover, because of the discrepancy in the kinetics of the bulk [Ca 2ϩ ] i and I BK , these results suggest that at least a fraction of the BK channels in somatotrophs responds to the rapid, high-amplitude increase in submembrane [Ca 2ϩ ] i in the vicinity of the VGCC (heretofore referred to as the domain [Ca 2ϩ ] i ).…”
Section: Rapid Activation Of Bk Channels By Domain [Ca 2؉ ] Imentioning
confidence: 99%
“…The 'effective' on and off rate constants for Ca2+ binding of Fura-2-loaded skeletal muscle fibres were 4-6 times smaller than those in vitro (2-7 x 108 M-1 s-1 and 84-97 s-1 respectively, Jackson, Timmerman, Bagshaw & Ashley, 1987;Kao & Tsien, 1988) due to binding of Fura-2 to the cytoplasmic proteins . If such a binding occurred in the ganglion cell, Focal depth for objectives used in epifluorescence measurements (Methods A and B) was measured by recording fluorescence from a drop of a Fura-2 solution (5 FM) placed in a plane (less than 2,um in thickness and 50 um in diameter) at different levels of the microscope stage ( Fig.…”
Section: Measurements Of Fura-2 Fluorescencementioning
confidence: 99%